2019
DOI: 10.31083/j.rcm.2019.02.52
|View full text |Cite
|
Sign up to set email alerts
|

The risk of periodontitis for peripheral vascular disease: a systematic review and meta-analysis

Abstract: Periodontitis is one of the risk factors associated with peripheral artery disease. This meta-analysis evaluates how periodontitis contributes to the pathogenesis and progression of peripheral artery disease. We systematically searched electronic databases Ovid Medline, Embase, Cochrane Library and Pubmed. Grey literature was also searched via Google Scholar. All studies evaluating the relationship between the incidence of periodontitis and peripheral artery disease were included. Subgroup analyses of carotid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Interestingly, greater subclinical carotid atherosclerosis has been reported to be associated with periodontitis in patients with systemic lupus erythematosus [ 16 ]. Moreover, periodontitis was found to be a significant risk factor for peripheral and carotid ASCVD in meta-analyses including large populations [ 17 , 18 , 19 ]. These observations suggest that pathological changes in oral microbiota composition and the related periodontitis may play a role in ASCVD pathophysiology by promoting chronic inflammation, dyslipidemia, including LDL-C oxidation [ 20 ], and the reduction of the antiatherogenic properties of high-density lipoprotein cholesterol (HDL-C) [ 21 ], endothelial-cell dysfunction [ 22 ], and, possibly, as-yet-unknown, additional pathological processes [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, greater subclinical carotid atherosclerosis has been reported to be associated with periodontitis in patients with systemic lupus erythematosus [ 16 ]. Moreover, periodontitis was found to be a significant risk factor for peripheral and carotid ASCVD in meta-analyses including large populations [ 17 , 18 , 19 ]. These observations suggest that pathological changes in oral microbiota composition and the related periodontitis may play a role in ASCVD pathophysiology by promoting chronic inflammation, dyslipidemia, including LDL-C oxidation [ 20 ], and the reduction of the antiatherogenic properties of high-density lipoprotein cholesterol (HDL-C) [ 21 ], endothelial-cell dysfunction [ 22 ], and, possibly, as-yet-unknown, additional pathological processes [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…All of these considerations led us to explore further factors which, in parallel or even independently of an excess of blood lipids, can determine the onset of or aggravate this low-grade chronic inflammation which, over time, also affects the arterial vessels. We then specifically refer to the dysbiosis of the oral and the intestinal microbiota [ 55 , 56 , 57 ], the latter of which has already been linked to dyslipidemia, inflammation and ASCVD [ 58 ].…”
Section: Low-grade Chronic Inflammation and Atherothrombosis: Clinica...mentioning
confidence: 99%
“…In a meta-analysis of 25 studies, including 22,090 participants, by Wang et al showed that PD increased the risk of PAD by 60% (OR = 1.60; 95% CI: 1.41–1.82, p < 0.001). Subgroup analysis showed that PD significantly increased the occurrence of lower extremity arterial disease and carotid artery disease (OR = 3.00; 95% CI: 2.23–4.04, p < 0.001 and OR = 1.39, 95% CI: 1.24–1.56, respectively, p < 0.001) [ 101 ]. Zeng et al, in a meta-analysis of 17,330 participants, showed that PD increased the risk of carotid atherosclerosis by 27% (OR: 1.27; 95% CI: 1.14–1.41, p < 0.001).…”
Section: Periodontal Disease and Risk Of Atherosclerosis Cardiovascul...mentioning
confidence: 99%
“… Effect of periodontal disease on the risk of atherosclerotic cardiovascular disease. Based on data from [ 96 , 97 , 98 , 101 , 102 , 106 , 111 ]. Abbreviations: ASCVD (atherosclerotic cardiovascular disease); VTE (venous thromboembolism); PAD (peripheral arterial disease); CAS (carotid artery stenosis); MI (myocardial infarction); CAD (coronary artery disease).…”
Section: Figurementioning
confidence: 99%